Sistema informático para la gestión de los procesos administrativos en la Dirección de Carreras de Ingeniería Eléctrica. - Sangoquiza Tonato, Mónica Maribel (2018)
The research project, about of development and implementation of a management computer system, which allows covering the need for the documentary management processes that are currently carried out manually in the Electrical Engineering Majors, for this, it will be implemented a system to automate the administrative processes that the Director usually does. This system is addressed to the director of the Electrical Engineering and teachers, allowing the Director to optimize several of his processes; besides facilitating communication and collaboration with tutors and teachers. It is developed through the PHP programming language, with a MYSQL database engine. Each process to develop the system, is documented, using the SCRUM methodology being a standard methodology more used for the analysis, implementation and documentation of object-oriented systems composed of three main phases, which are: Pre-Game, Game, Post- Game that allow give to know the development of the system in a general way in order to deliver a quality software system that meets the needs of the client. Besides helps to carry of an orderly the development of each requirement specified by the direction of the major of Electrical Engineering belonging to the Faculty of Ciencias de la Ingenieria Y Aplicadas of the Univeridad Técnica de Cotopaxi. Obtaining as a result a computer system for the management of the processes of the Electrical Engineering major composed of the following modules: User profiles, News: allows the creation of the news by the major Coordinator, Academic period, Notes, Titration. In order to put the system into production, it is hosted in a hosting thus that teachers can access the web and go up files from anywhere.